THE CONTRIBUTION OF LEARNING MOTIVATION AND READING COMPREHENSION SKILL TOWARD WRITING BIOGRAPHY TEXT SKILL (KONTRIBUSI MOTIVASI BELAJAR DAN KETERAMPILAN MEMBACA PEMAHAMAN TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI) - Wilda Fathia; Wahidah Fitriani; Diyana Kamarudin (Universitas PGRI Sumatera Barat, 2021)
The purpose of this research was to describe some of the following. (1) The contribution of learning motivation of writing biography text of students. (2) The contribution of reading comprehension skill of writing biography text of students. (3) The contribution of learning motivation and reading comprehension skill together to writing biography text of students of class VIII Junior High School in Pesisir Selatan. This research was a quantitative research using correlational method. The population was class VIII students Junior High School of Pesisir Selatan Regency. The sample is 110 students. Techniques to data analysis using Pearson Product Moment Correlational test, multiple regression, t test, and F test. The results of the research are. 1) The learning motivation contribute significant by 20% to writing biography text. 2) The reading comprehension skill contribute significant by 37.5% to writing biography text. 3) The learning motivation and reading comprehension skill together contribute by 38% to the writing biography text. Based on the result of the research, can conclusion is learning motivation and reading comprehension skills together contribute and significant relationship to writing biography text skills.